STUDY ON LENGTH-WEIGHT RELATIONSHIPS AND REPRODUCTIVE BIOLOGY OF SYNODONTIS NIGRITA (VALENCIENES, 1840) IN KANGIMI RESERVOIR, KADUNA STATE, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2021)
The length-weight relationships and reproductive biology of Synodontis nigrita was studied. Fish specimens were collected from fishermen catch at the landing site.  Estimated exponent (b) varied between 1.949 and 2.845 (2.3092Â±0.08). Correlation (0.915Â±0.01) between length and weight indicated a strong positive relationship. There were more females than males in the fish species, the difference was not significant (P>0.05). Male fish recorded gonadosomatic index range from 0.253Â±0.03 to 2.715Â±0.15 and 0.410Â±0.05 to 5.352Â±0.72 for females. The gonadosomatic index of the male fish was not significantly different from that of the female. Rainy months gonadosomatic index were significantly higher than the dry months (P
Keywords: LWR, Sex Ratio, Synodontis nigrita